An evaluation of teacher candidates' opinions about art education and form-meaning relationship - ABACI, OYA (ELSEVIER SCIENCE BV, 2015)
We live in an age in which visuality is important. In this day and time, instead of long texts and narrations, incarnated forms of meaning and notions are used for informational transfer. As to the reach of an individual for abstract notions, it is a competence of that individual which is gained by the education. Due tothe indispensable contributions of art education classes have on an individual's reasoning and imagination, they also directly contribute to development of said individual's cognitive abilities. This research aims to evaluate the ability of thinking in expressible meanings of forms, examined among the tea cher candidates who took visual arts education and art and aesthetics class in 2012-2013 academic year, majoring in pre-school teaching and social studies teaching respectively. Purpose is to present how teaching candidates develop the form-meaning relationship. A total of 298 teacher candidates were involved in the research. Symbols such as circle, triangle, square, tree, pencil, hand, fish, flying bird, wheel, bitten apple, and yin-yang were shown to these teacher candidates before and after 12 weeks curriculum, and it is asked from them to answer the question of what these symbols are and what may them express. Finally, answers were evaluated using qualitative research model. (C) 2015 The Authours. Published by Elsevier Ltd.
Keywords: Art; Art Education; Form and Meaning; Visual Perception; Visual Thinking